Acceptance and adoption of ChatGPT in higher education: a systematic review - Morales Ramírez, Alejandra (2025)
Introduction: Generative artificial intelligence, such as ChatGPT, has transformed higher education by facilitating autonomous learning and content creation, while also posing challenges in ethics, assessment, and academic integrity. Objective: This research aims to identify the theoretical models, analyzed factors, research methods, sampling approaches, and data analysis techniques used in studies on ChatGPT in higher education. Method: A systematic literature review following the PRISMA protocol was conducted using ScienceDirect, PubMed, and EBSCO (September 2023 – September 2024); quality criteria from JBI and those proposed by Ijaz and Yadegaridehkordi (2024) were applied, resulting in the selection of 27 studies, mostly from Asia. Results: The findings indicate a predominance of quantitative approaches based on surveys and statistical analyses, with Structural Equation Modeling (SEM) and Confirmatory Factor Analysis (CFA) as the most frequent techniques, while convenience sampling was the most commonly used method. Discussion: Perceived usefulness, social influence, and behavioral intention emerged as key factors in its adoption; therefore, it is recommended to expand research to other regions and to establish policies that ensure its responsible use in education.